The Moderating Role of Perceived Risk in Social Media Marketing’s Impact on Customer Engagement, e-WOM, and Online Repurchase Intention in E-Commerce : Integrating ELM and SOR Models - Aggarwal, Priyanka; Chauhan, Kavita; Chaturvedi, Vijit (Prabandhan: Indian Journal of Management, 2025)
Purpose : The empirical study investigated the impact of social media marketing activities (SMMA) on customer engagement (CE), e-WOM, and online repurchase intention (ORPI) in e-commerce. Methodology : The data from 386 Indian social media users was analyzed using structural equation modeling (SEM) based on the elaboration likelihood model (ELM) and stimulus–organism–response (SOR) frameworks. Findings : The study found that SMMA significantly influenced cognitive and affective aspects of engagement. Affective engagement (AE) positively affected both e-WOM and ORPI. Perceived risk (PR) considerably moderated the relationships between SMMA and cognitive engagement (COG). It also moderated the relation of COG and AE with ORPI, while PR did not moderate the relationship of SMMA & AE or AE & e-WOM or COG & e-WOM. Implications : This current study discussed how various forms of engagement affected specific purchase behaviors like e-WOM and ORPI. We also underlined the role of PR in forming COG and AE to drive those behaviors. By scrutinizing these relationships between the SOR and ELM frameworks, the study significantly contributed to the existing knowledge. Originality : This study offered valuable insights for e-commerce businesses to design effective SMM strategies and manage CE, especially in the presence of PR. It also outlined whether companies should adopt the central or peripheral route of the ELM when designing such strategies.